Feasibility of Electric Vehicle: Electricity by Grid ï¿½ Photovoltaic Energy - Castro, Thais Santos [UNESP]; de Souza, Teï¿½filo Miguel [UNESP]; Silveira, Josï¿½ Luz [UNESP] (Elsevier, 2017)
Among the actual available ways for power generation solar energy is remarkable because it has proven great development it is an economically viable alternative it is environmentally accepted and it has high reliability and low maintenance. A discussion covers the solar energy; electric vehicles an alternative to traditional internal combustion engines driven vehicles; dimensioning of a photovoltaic plant to provide energy supply for the Daimler electric car Smart Fortwo considering four different situations i.e. driving the car during seven days five days three days and one day a week; and the economic feasibility of a photovoltaic system installation to supply energy to an electric vehicle.
Keywords: Electric vehicle; Investment; Photovoltaic; Power distribution company; Solar module